Clarifying the preferential occupation of Ga3+ ions in YAG:Ce, Ga nanocrystals with various Ga3+-doping concentrations by nuclear magnetic resonance spectroscopy. Issue 45 (7th November 2016) - He, Xiaowu; Liu, Xiaofang; You, Congya; Zhang, Yongzhe; Li, Rongfeng; Yu, Ronghai
Abstract : Preferential substitution of Ga 3+ ions for octahedral Al 3+ ions in YAG:Ce, Ga nanophosphors enhances the luminescence properties of Ce 3+ activators. Abstract : As candidates for display and lighting optical materials, yttrium aluminum garnet nanophosphors co-doped with Ce 3+ and Ga 3+ ions (YAG:Ce, Ga) were successfully synthesized via a facile sol–gel method. We used multiple characterization techniques to study the local crystal structure of Ce 3+ activators and examine the preferential position of Ga 3+ ions in YAG:Ce, Ga nanophosphors. For the first time, solid-state nuclear magnetic resonance spectroscopy was used to confirm that Ga 3+ ions preferentially replaced the octahedral Al 3+ ions in a wide Ga 3+ concentration range. The replacement caused the expansion of the lattice constant and decreased the local crystal field strength surrounding Ce 3+ activators that located in the dodecahedral sites, which were beneficial to the luminescence emission of Ce 3+ ions. The YAG:Ce, Ga nanophosphors with excellent photoluminescence properties were obtained by optimizing the calcination temperature (930 °C) and Ga 3+ -doping concentration (18 at%). The optimized nanophosphors displayed stronger luminescence emission with a desirable blue shift than classic YAG:Ce phosphors, and presented a short fluorescence lifetime of ∼24 ns and a long fluorescence lifetime of ∼85 ns.